The effect of channel slope angle on breastshot waterwheel turbine performance by numerical method - Dendy Adanta; Budiarso; Warjito (Energy Reports, 2020)
This study examined the effect of the water channel slope angle on breastshot waterwheel turbine performance using the computational fluid dynamics method with six-degrees of freedom (6-DoF) feature. The method and 6-DoF feature were chosen because turbine rotation is a computational result and the flow pattern can be represented more precisely. Computational results using the 6-DoF feature were used as the basis for recommending a ratio of rotational velocity for a wheel ( U) with an inlet velocity (W), or U/W, for turbine design. Five slope angles were analysed, and the results indicated higher efficiency was produced by a 10° slope angle while the lowest was 25°. Based on results, a higher slope angle channel could cause losses or leakage due to water leading to a gap between the wheel and channel. As such, a method of increasing the kinetic energy of water by modifying the channel shape, such as having an angle, requires additional attention to the water velocity direction. Moreover, stable efficiency occurs in a ratio of U/W between 1.1 - 1.6. Thus, it is estimated that the optimum turbine design recommended for U being 1.1 to 1.6 times W.
Keywords: 330; Breastshot; Waterwheel; Computational